Triple Frontier: Change and Continuity on the Riverfront - Wilcox, Robert (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
Book Review Jacob Blanc and Frederico Freitas, eds. Big Water: The Making of the Borderlands between Brazil, Argentina, and Paraguay. (Tucson: University of Arizona Press, 2018).